Study of The Impact of Coastline Changes on Coastal Settlement Areas Along th East Coast of Minahasa - Fela, Warouw; Dwight, Rondonuwu; Julianus, Sondakh (Devotion : Journal of Research and Community Service, 2024)
The natural phenomenon of abrasion on the east coast of Minahasa which occurred from 1980 to 2020 has brought about changes in the coastline which then threatens the existence of coastal residential areas. Land function data in this study uses data sourced from the USGS (United States Geological Survey) Landsat-5 TM Imagery web and also Google Earth Pro Data, the data is in the form of historical image data with 10-year intervals and starting from 2003 to 2023. In 20 years there has been an increase in the area of built-up land for settlement functions in each village. The function of plantation land has been reduced in area as a result of settlement development. Meanwhile, sandy coastal land has also experienced a reduction in area as a result of sea waves and abrasion. The results showed that Atep Oki Village had experienced the farthest coastal setback of 42.28 m, while Kamenti Village and Parentek Village, respectively as far as 27.27 m and 23.33 m. These findings have confirmed the impact of waves that damaged the coast of Atep Oki village in 2013. It also shows that the abrasion process will be continue on the coast of Atep Oki village and its surroundings. The measured coastline setback distance is around 23 - 43 meters which causes a reduction in the area of residential land as well as damage to house buildings, road infrastructure and boundary embankments. Residents must move their residence to an area that is safer from the threat of waves and abrasion processes. Damaged house buildings especially those made of wood and plywood require repair costs while most residents have limited income as farmers, cultivators and fishermen. This condition causes the threat of loss of living environment and increased spending due to abrasion disaster adaptation efforts.